Pendampingan Strategi Marketing di Era Digital bagi Usaha Mikro Kecil Menengah Masyarakat Desa Bulangan Gresik - Latifah, Eny; Suroso, Suroso; Martiwi, Wanala Abdillaika; Mu’minah, Rina Ummatul; Ningsih, Fila Wahyu; Fadlilah, Eva Shofiyatul; Lestari, Dewi Ayu; Salsabila, Wilda Salma; Hashin, Muhammad Hishin Al; Nurah, Nurah (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This community service aims to provide assistance to the people of Bulangan Gresik Village in determining the right strategy for marketing for the MSME sector. The method used is PAR (Participatory Action Research). The service stages start from preliminary research, acculturation, community organizing for the research agenda, action planning for social change, action, and evaluation. The results of the service are (1) Education through seminars on the introduction of packaging and branding; (2) Providing training for product branding and product packaging; (3) Training to create marketplace accounts such as Shoppe, Lazada, Bukalapak; (4) maximizing social media such as Whats App, Instagram, Telegram, Tiktok for digital marketing promotions, (5) Establishing collaboration with traditional and modern industries and stalls.